Synthesis of chitosan/AC/Fe3O4 nanocomposite and its structural, magnetic, and heavy metal adsorption characteristics - Febrianti, Berliana Ayu; Pujiarti, Herlin; Subadra, Ulfawanti Intan; Taufiq, Ahmad (Eclética Química, 2026)
The chitosan/activated carbon (AC)/Fe3O4 nanocomposite has been successfully synthesized. The nanocomposite was then characterized to investigate its structural, magnetic, and heavy metal Cr(III) adsorption characteristics using XRD, SEM, FTIR, VSM, and ICP-OES. The chitosan/AC/Fe3O4 nanocomposite performed a single phase with a cubic inverse spinel structure with a lattice parameter and crystallite size of 8.38 ± 0.01 Å and 5.04 ± 0.09 nm, respectively. The SEM image showed that the morphology of chitosan/AC/Fe3O4 tended to be spherical with an average particle size of 51.4 ± 0.4 nm. The FTIR spectrum showed that the chitosan/AC/Fe3O4 nanocomposite exhibited the presence of a β-1,4-glycosidic bond at 858 cm–1 originating from chitosan. The C=C functional group and Fe-O bonds appeared at 1606 and 439–642 cm–1, indicating the presence of AC and Fe3O4. The chitosan/AC/Fe3O4 nanocomposite had superparamagnetic properties with a saturation magnetization value of 36.27 ± 0.05 emu/g. Furthermore, the chitosan/AC/Fe3O4 nanocomposite had a capacity and efficiency for Cr(III) adsorption of 13.95 mg/g and 27.88% at a contact time of 240 min, respectively.